2015 International Conference on Mechanics - Seventh Polyakhov's Reading 2015
DOI: 10.1109/polyakhov.2015.7106722
|View full text |Cite
|
Sign up to set email alerts
|

A Matlab tool for regions of attraction estimation via numerical algebraic geometry

Abstract: For a locally stable polynomial dynamical system its region of attraction can be estimated by a polynomial Lyapunov function level set. We formulate this problem in terms of global minimization of a polynomial function over single polynomial constraint. We describe a simple Matlab tool, which employs numerical algebraic geometry methods for computing all local solutions of the optimization problem and therefore its global solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Buchberger's algorithm generalizes algorithms: Gaussian elimination for a system of linear algebraic equations and Euclid's algorithm for calculating the greatest common divisor of a set of one-dimensional polynomials. is algorithm was implemented on computers in symbolic computation programs using Gröbner bases for solving systems of polynomial equations [10][11][12].…”
Section: Gröbner Basesmentioning
confidence: 99%
“…Buchberger's algorithm generalizes algorithms: Gaussian elimination for a system of linear algebraic equations and Euclid's algorithm for calculating the greatest common divisor of a set of one-dimensional polynomials. is algorithm was implemented on computers in symbolic computation programs using Gröbner bases for solving systems of polynomial equations [10][11][12].…”
Section: Gröbner Basesmentioning
confidence: 99%
“…There, we consider first-order optimality conditions of L in the test on Line 6, but switch to the Newton method on the first-order optimality conditions of (7), while memorising the current value. While minimising (7), we check the active set; when it does change, we revert to solving the convexification with the memorised value. Although this Figure 1: The motivation: the evolution of infeasibility (top row) and objective function (bottom row) when one switches from solving the convexification to the Newton method after a given number of steps on IEEE 30-bus test system (left), 118-bus test system (middle), and a snapshot of the Polish system (case2383wp; right).…”
Section: It Is Well-known That One Can Constructmentioning
confidence: 99%
“…Recently, Henrion and Korda [12] have shown that the domain of monotonicity of a polynomial system can be computed by solving an infinitedimensional linear program over the space of measures, whose value can be approximated by a certain hierarchy of convex semidefinite optimisation problems. See also the work of Valmórbida et al [29,28,27] in the context of partial differential equations, and elsewhere [7]. Dvijotham et al [9,10] showed that it can also be be cast as a certain non-convex semidefinite optimisation problem.…”
Section: Related Workmentioning
confidence: 99%